2002
DOI: 10.1007/s00330-002-1627-4
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis of the breast

Abstract: We report a case of sarcoidosis of the breast in a 31-year-old woman who presented with a palpable breast mass. The mammography showed a spiculated mass without any microcalcifications. Ultrasonogram showed a hypoechoic mass. Computed tomography showed a spiculated nodule. T2-weighted MR images with fat-suppression technique showed a mass with irregular border that appeared to be an accumulation of small nodules. Gadolinium-enhanced dynamic study showed gradually increasing signal intensity. She underwent exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 4 publications
(6 reference statements)
1
29
0
Order By: Relevance
“…Ishimaru et al, reported a case of breast sarcoid presenting as an irregular mass which demonstrated slow progressive enhancement on serial post contrast MRI imaging. [5] However, other authors have reported breast sarcoid lesions demonstrating rapid enhancement with wash-out phenomenon which is commonly seen in breast carcinoma, making sarcoid lesions very difficult to distinguish from cancer. [1]…”
Section: Discussionmentioning
confidence: 99%
“…Ishimaru et al, reported a case of breast sarcoid presenting as an irregular mass which demonstrated slow progressive enhancement on serial post contrast MRI imaging. [5] However, other authors have reported breast sarcoid lesions demonstrating rapid enhancement with wash-out phenomenon which is commonly seen in breast carcinoma, making sarcoid lesions very difficult to distinguish from cancer. [1]…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Mammograms may be completely negative. 6 Microcalcifications associated with breast sarcoid have not been reported previously. 6 Ultrasound findings may also be indicative of malignancy with irregular hypoechoic masses being most common, although non-specific findings are more common.…”
Section: Sarcoid Of the Breast Associated With Microcalcifications Onmentioning
confidence: 92%
“…5 Only two case reports discuss magnetic resonance imaging findings describing non-specific findings. 6…”
Section: Sarcoid Of the Breast Associated With Microcalcifications Onmentioning
confidence: 99%
“…Mammographic fi ndings can range from a spiculated mass suspicious for carcinoma to an ill-defi ned or irregular lesion (3,4). Microcalcifi cations are not associated with sarcoidosis (6). Th e ultrasound appearance can be variable, but typically demonstrates irregular hypoechoic masses (4).…”
Section: Diagnosis Of Sarcoidosis From a Biopsy Of A Dilated Mammary mentioning
confidence: 99%